Chemoproteomic Profiling of Phosphoaspartate Modifications in Prokaryotes. (7th November 2018) - Chang, Jae Won; Montgomery, Jeffrey E.; Lee, Gihoon; Moellering, Raymond E.
Abstract: Phosphorylation at aspartic acid residues represents an abundant and critical post‐translational modification (PTM) in prokaryotes. In contrast to most characterized PTMs, such as phosphorylation at serine or threonine, the phosphoaspartate moiety is intrinsically labile, and therefore incompatible with common proteomic profiling methods. Herein, we report a nucleophilic, desthiobiotin‐containing hydroxylamine (DBHA) chemical probe that covalently labels modified aspartic acid residues in native proteomes. DBHA treatment coupled with LC‐MS/MS analysis enabled detection of known phosphoaspartate modifications, as well as novel aspartic acid sites in the E. coli proteome. Coupled with isotopic labelling, DBHA‐dependent proteomic profiling also permitted global quantification of changes in endogenous protein modification status, as demonstrated with the detection of increased E. coli OmpR phosphorylation, but not abundance, in response to changes in osmolarity.